2021
DOI: 10.1016/j.envint.2020.106343
|View full text |Cite
|
Sign up to set email alerts
|

The influence of chemical composition, aerosol acidity, and metal dissolution on the oxidative potential of fine particulate matter and redox potential of the lung lining fluid

Abstract: Highlights Oxidative potential (OP) of PM 2.5 from Canadian cities was studied using a new acellular chemical assay. Redox potential of simulated lung fluid was highly associated with all physiological OP indicators. Traffic emissions had the highest OP, followed by industrial emissions and crustal matter. OP was strongly associated with black carbon and transition metals, especially Cu, Fe, Mn, and Ti.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 102 publications
(97 reference statements)
1
38
0
1
Order By: Relevance
“…While Fe exhibited a low solubility, it is the most abundant soluble metal, followed by Zn, Ba, Cu, Mn, and Sb. This is important, as water-soluble Fe and other transition metals, specifically metals associated with brake/tire wear (i.e., copper), have been directly correlated to ROS production [24,28]. Furthermore, other studies also reported associations between ROS activity and water-soluble brake wear elements (Cu, Ba) in coarse particles [23,46].…”
Section: Water-soluble Metal(oids)mentioning
confidence: 96%
See 2 more Smart Citations
“…While Fe exhibited a low solubility, it is the most abundant soluble metal, followed by Zn, Ba, Cu, Mn, and Sb. This is important, as water-soluble Fe and other transition metals, specifically metals associated with brake/tire wear (i.e., copper), have been directly correlated to ROS production [24,28]. Furthermore, other studies also reported associations between ROS activity and water-soluble brake wear elements (Cu, Ba) in coarse particles [23,46].…”
Section: Water-soluble Metal(oids)mentioning
confidence: 96%
“…This behavior can be due to the diverse sources dominated abrasion or hot-vapor condensation particles, or me onto the surface of other particles and, thus, tend to be more l within crustal material. For example, a relatively high solubilit tributed to its high-temperature industrial sources (See Section 3 low solubility, it is the most abundant soluble metal, followed by This is important, as water-soluble Fe and other transition meta sociated with brake/tire wear (i.e., copper), have been directly co tion [24,28]. Furthermore, other studies also reported associatio and water-soluble brake wear elements (Cu, Ba) in coarse particl A number of these metal(oids) are typically in the form of ox and, thus, have varying solubility depending on their specific fo Figure 4, slightly lower water-solubility was observed for bra PM2.5 collected in Vancouver.…”
Section: Water-soluble Metal(oids)mentioning
confidence: 99%
See 1 more Smart Citation
“…CC BY 4.0 License. Shahpoury et al, 2021). In addition, the oxidant content of ambient aerosol particles controls their ageing time scales and interactions with the biosphere (Pöschl and Shiraiwa, 2015).…”
Section: Ros Budgets and Oxidative Potential (Op)mentioning
confidence: 99%
“…Fang et al [119] demonstrated almost in a Venn-diagram way that watersoluble Cu was found only the presence of highly acidic sulfates (see Figure 6). Noticeable correlation between water-soluble Fe, pH, and concentrations of sulfate SO 4 2− in Toronto, Montreal, and Vancouver, which suggested that acid processing contributed to Fe solubility in the aerosol aqueous phase [134]. Similarly, Brehmer et al [135] confirmed that elements associated with the secondary sulfate source (As, Mo, Zn) had the strongest correlation with increased cellular oxidative potential, while chemical markers of biomass burning (water-soluble K and water-soluble OC) had negligible OP.…”
Section: Role Of Metals In Oxidative Stress and Inflammationmentioning
confidence: 99%